2016
DOI: 10.4028/www.scientific.net/msf.854.65
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sheet Thickness, Loading Rate and Punch Diameter on the Deformation Behaviour of AZ31 during 3-Point Bending

Abstract: In this study, the influence of sheet thickness, loading rate, and punch diameter on the bending behaviour of twin-roll cast, rolled and heat-treated AZ31 magnesium alloy was investigated. Therefore, the 3-point bending test was performed at room temperature using an electromechanical testing machine (v = 0.1−10 mm/s) with different punch diameters (D = 2 mm, 8 mm, 16 mm). The initial material has a recrystallized microstructure with grain sizes of 6−9 µm. It is shown by the mechanical investigations that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…The results showed that when the sheet was heated above 200 °C, the yield stress of the material was significantly reduced, showing good high-temperature formability. At present, the research of magnesium alloy sheet bending process is mainly focused on the AZ series magnesium alloy, and most of the research is the AZ31 magnesium alloy, while the research of rare earth magnesium alloy is less prominent [13,14]. While AZ series magnesium alloys have many advantages, they also have shortcomings, including low strength, unstable quality, and poor heat resistance, and the addition of rare-earth elements can improve their performance significantly [15][16][17].…”
Section: Finite Element Simulation Of U-bending Of High-strength Mg-g...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that when the sheet was heated above 200 °C, the yield stress of the material was significantly reduced, showing good high-temperature formability. At present, the research of magnesium alloy sheet bending process is mainly focused on the AZ series magnesium alloy, and most of the research is the AZ31 magnesium alloy, while the research of rare earth magnesium alloy is less prominent [13,14]. While AZ series magnesium alloys have many advantages, they also have shortcomings, including low strength, unstable quality, and poor heat resistance, and the addition of rare-earth elements can improve their performance significantly [15][16][17].…”
Section: Finite Element Simulation Of U-bending Of High-strength Mg-g...mentioning
confidence: 99%
“…The results showed that when the sheet was heated above 200 • C, the yield stress of the material was significantly reduced, showing good high-temperature formability. At present, the research of magnesium alloy sheet bending process is mainly focused on the AZ series magnesium alloy, and most of the research is the AZ31 magnesium alloy, while the research of rare earth magnesium alloy is less prominent [13,14].…”
Section: Introductionmentioning
confidence: 99%